Geochronology and Genesis of the Tiegelongnan Porphyry Cu(Au) Deposit in Tibet: Evidence from U–Pb, Re–Os Dating and Hf, S, and H–O Isotopes. Issue 1 (January 2017) - Lin, Bin; Tang, Ju‐Xing; Chen, Yu‐Chuan; Song, Yang; Hall, Greg; Wang, Qin; Yang, Chao; Fang, Xiang; Duan, Ji‐lin; Yang, Huan‐Huan; Liu, Zhi‐Bo; Wang, Yi‐Yun; et al.
Abstract: The Tiegelongnan Cu (Au) deposit is the largest copper deposit newly discovered in the Bangong–Nujiang metallogenic belt. The deposit has a clear alteration zoning consisting of, from core to margin, potassic to propylitic, superimposed by phyllic and advanced argillic alteration. The shallow part of the deposit consists of a high sulphidation‐state overprint, mainly comprising disseminated pyrite and Cu–S minerals such as bornite, covellite, digenite, and enargite. At depth porphyry‐type mineralization mainly comprises disseminated chalcopyrite, bornite, pyrite, and a minor vein molybdenite. Mineralization is disseminated and associated with veins contained within the porphyry intrusions and their surrounding rocks. The zircon U–Pb ages of the mineralized diorite porphyry and granodiorite porphyry are 123.1 ± 1.7 Ma (2σ) and 121.5 ± 1.5 Ma (2σ), respectively. The molybdenite Re–Os age is 121.2 ± 1.2 Ma, suggesting that mineralization was closely associated with magmatism. Andesite lava (zircon U–Pb age of 111.7 ± 1.6 Ma, 2σ) overlies the ore‐bodies and is the product of post‐mineralization volcanic activity that played a critical role in preserving the ore‐bodies. Values of −4.6 ‰ to + 0.8 ‰ δ 34 S for the metal sulfides (mean − 1.55 ‰) suggest that S mainly has a deep magmatic source. The H and O isotopic composition is (δD = −87 ‰ to −64 ‰; δ 18 OH2O  = 5.5 ‰ to 9.0 ‰), indicating that the ore‐forming fluids are mostly magmatic‐hydrothermal, possibly mixed with a small amount of meteoric water. The zircon εHf (t) of the diorite porphyry is 3.7 to 8.3, and the granodiorite porphyry is 1.8 to 7.5. Molybdenite has a high Re from 382.2 × 10 −6 to 1600 × 10 −6 . Re and Hf isotope composition show that Tiegelongnan has some mantle source, maybe the juvenile lower crust from crust–mantle mixed source. Metallogenesis of the Tiegelongnan giant porphyry system was associated with intermediate to acidic magma in the Early Cretaceous (~120 Ma). The magma provenance of the Tiegelongnan deposit has some mantle‐derived composition, possibly mixed with the crust‐derived materials. Abstract : Two types of mineralization and three types of alteration identified in the Tiegelongnan porphyry Cu (Au) deposit. Precise geochronology research on ore-bearing porphyries and the mineralization. H‐O‐S isotopes suggest magmatic source. Lu‐Hf isotopes of zircons suggest a juvenile lower crust from crust‐mantle mixed source.